The neutralization of Southeast Asia. Forew. by G.T. Hsiao (Praeger Publishers, 1975)
With index and tabs. Published in cooperation with the Asian Studies Program of Southern Illinois University at Edwardsville. Dick Wilson is pseud. of Richard Garratt.